EVALUATION OF THE PHYSICOCHEMICAL QUALITY OF RAW AND TREATED WASTEWATER IN THE CITY N’GOUSSA AND THE POSSIBILITY OF THEIR - A., . Seddiki*1; S, . Kateb2 (university of eloued جامعة الوادي, 2020)
The reuse of treated wastewater in agriculture in Ouargla is encouraging but requires monitoring and further study to encourage the valorization of treated water in the entire agricultural sector of the basin of Ouargla.The objective of this study is to monitor the physico-chemical quality of raw and purified wastewater from the N 'GOUSSA WWTP in order to detect any anomalies that may exist in the WWTP and to be able to reuse the treated water for irrigation. . The physicochemical results obtained revealed that the raw wastewater entering the treatment plant exhibits fairly high organic and nitrogen pollution. Removal of MES and nitrogen compounds appears inefficient due to the massive proliferation of implanted filters.
artical
Keywords: wastewater treatment; Reed plant filter; arid environment; physico-chemical parameters; Abatement rate